# How do you solve this for r....?

2k+ar=r-3y

### 3 Answers

Relevance

- Anonymous1 decade agoBest Answer
✰Answer✰

r = (-3y - 2k)/(a - 1)

✐Derivation✐

2k + ar = r - 3y

Try different ways to find the value of r. Isolating r variables is the better way to solve for r.

ar = r - 3y - 2k

ar - r = -3y - 2k

Factor the left side.

r(a - 1) = -3y - 2k

r = (-3y - 2k)/(a - 1)

- Anonymous1 decade ago
2k + 3y = r - ar

2k + 3y = r( 1 - a)

r = (2k + 3y) / ( 1 - a)

Still have questions? Get your answers by asking now.